English Foreign Language Teachers’ Perception on The Use of Information and Communication Technology in Teaching English at SMKN 3 Langsa - Nurul Fitri; Afrida , Nina; Meutia, Cut Intan (Journal of linguistics, culture and communication, 2024)
This study aimed to explore English as a Foreign Language (EFL) teachers' perceptions of Information and Communication Technology (ICT) use in the English language teaching and learning process. The main purpose of this article is to explore the challenges of teacher face in using ICT. Two experienced teachers, recognized for their ICT integration, selected as the research subjects at SMK Negeri 3 Langsa. Employing a qualitative approach with a phenomenological design, data was collected through semi-structured interview. The findings reveal that both teachers acknowledge the positive role of ICT in enhancing teaching efficiency, student engagement, and diversifying learning resources. Despite encountering technical challenges, such as network disruptions, both teachers advocate for continuous teacher training, increased investment in ICT infrastructure, and innovative research to optimize ICT integration in English language teaching, ultimately contributing to a more effective learning environment.